Reinforcing customer loyalty through service employees' competence and benevolence. Issue 13 (25th October 2016) - Nguyen, Nha
ABSTRACT: The present study aims to investigate how service employees' competence and benevolence can influence customer loyalty. A hierarchical multiple regression with interaction analysis was performed on data collected from 1296 customers in a financial service provider. The results show a significant interaction between competence and benevolence in their influence on customer loyalty. These results reinforce the idea that benevolence can be used to enhance the effect of competence on customer loyalty. The managerial and research implications of the reported study are discussed.